Development drivers for urban regeneration and livability in worn-out neighborhoods - Hedayatnezhad Kashi, Seyed Mostafa; Hashemkhani Zolfani, Sarfaraz; Ghane, Mahsa; Antuchevičienė, Jurgita; Trinkūnas, Vaidotas (International Journal of Strategic Property Management, 2025)
Development driver projects are recognized as tools for revitalizing and regenerating worn-out urban fabrics. Recent studies emphasize the importance of development driver projects for regeneration across three scales: macro, medium, and micro. However, research has lacked an examination of the impact of indicators at all three scales. To fill this research gap, the present study investigates the effect of development driver indicators on the regeneration of the worn-out fabric of Semnan, one of Iran’s historic and significant cities. This research initially identifies 16 indicators across the three scales. Data were collected from 385 residents and analyzed using the Phi coefficient and structural equation modeling. The results of the Phi test indicated that development projects could act as “nuclei for urban transformation of the worn-out fabric of Semnan”. Furthermore, the structural equation modeling analysis revealed that development driver indicators at the macro scale, such as parks (0.71) and landscape design (0.66), have a significant impact on regeneration. This study emphasizes the importance of a comprehensive approach to regeneration and suggests that active stakeholder participation in various stages of regeneration is essential. The findings of this study can serve as guidance for policymakers and urban planners in Iran and other countries.